Liquid Hydrocarbon Fuel Collected from Waste Plastic by Using CUCO3 Catalyst - Singh, Manvir; Kumar, Sudesh; Sarker, Moinuddin (SCHOOL SCIENCE, 2017)
Plastics have many properties like light weight, high durability, so demands increase in every sector. Plastics include carbon, hydrogen, nitrogen, oxygen, sulfur and halogen atoms. The main thing which makes plastics waste valuable is longer carbon chains than those in gasoline and diesel fuels. Therefore, it is possible to convert waste plastic into liquid hydrocarbon fuels. This research paper aims to solve the twin problem of environment pollution due to plastics and the need for an alternative liquid hydrocarbon fuel source. Pyrolysis of the waste plastic bag (hdpe) was carried out with catalysts. The collected liquid hydrocarbon fuels were characterised by FT-IR spectroscope, NMR spectroscope and conversion was very good.